Akademik Doleček / Academician Doleček - Hodžić, Muamer (Pregled: časopis za društvena pitanja / Periodical for social issues, 2016)
This text is an overview of a book by Vlatko Doleček Od đaka pješaka do akademika (From Walking Schoolboy to Academician), Udruţenje obrazovanje gradi BiH, Sarajevo, 2014.